Students’ Perception of Their Social Responsibility in Relation to The University – A Pilot Study Report - Edyta SPODARCZYK; Katarzyna I. SZELAGOWSKA-RUDZKA (Communications of International Proceedings, 2020)
This pilot study aimed to identify characteristics (in self-assessment) distinguishing socially responsible students (SRS) in their relations with the university and how much these features correspond to SRU dimensions (values, relations, graduate, education, efficient organization) and depend on gender, level and year of study and type of university (public, private). In the respondents’ opinions, the most important features of a socially responsible student are showing respect to lecturers, administrative staff and other students; accepting the cultural and national differences of other members of the academic community; respecting the rules of personal culture and being guided by truth and honesty while assessing lecturers and classes. These features refer to the dimension of value, being a basis for shaping other SRU dimensions and the related attributes of a responsible student. It is also a basis for building the right attitude of future graduates, aware of their responsibility for their future decisions and actions. The identified differences relating to older students, graduate studies and private universities do not distort the main conclusion. Since this is a pilot study, conclusions refer only to the studied universities. However, they indicate an interesting direction for further valuable research in this field.
Keywords: social responsibility of universities (SRU); dimensions of SRU; socially responsible student; characteristics of a socially responsible student; public; private university.